Human immunodeficiency virus type 1 envelope glycoprotein is modified by O-linked oligosaccharides. - Bernstein, H B (1994)
The human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein has been shown to be extensively modified by N-linked glycosylation; however, the presence of O-linked carbohydrates on the glycoprotein has not been firmly established. We have found that enzymatic deglycosylation of the HIV-1 envelope glycoprotein with neuraminidase and O-glycosidase results in a decrease in the apparent molecular weight of the envelope glycoprotein. This result was observed in both vaccinia virus recombinant-derived envelope glycoproteins and glycoproteins derived from the IIIB, SG3, and HXB2, strains of HIV-1. The decrease in molecular weight was also observed when the envelope glycoprotein had been deglycosylated with N-glycanase F after treatment with neuraminidase and O-glycosidase, indicating that the decrease in apparent molecular weight was not attributable to the removal of N-linked carbohydrate. Treatment with neuraminidase, O-glycosidase, and N-glycanase F was found to be necessary to remove all radiolabel from [3H]glucosamine-labelled envelope glycoprotein, a result seen for both recombinant and HIV-1-derived envelope glycoprotein. [3H]glucosamine-labelled carbohydrates liberated by O-glycosidase treatment were separated by paper chromatography and were found to be of a size consistent with O-linked oligosaccharides. We, therefore, conclude that the HIV-1 envelope glycoprotein is modified by the addition of O-linked carbohydrates.